PUBLIC PERCEPTIONS OF HEALTHCARE SERVICE QUALITY: A COMPARATIVE ANALYSIS OF GOVERNMENT AND PRIVATE HOSPITALS - Mohanty, Kasturi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Now a day’s competitive healthcare landscape, service quality is crucial for hospital survival and reputation. Globalization has reshaped expectations of people. They are demanding efficient, high-quality care medical care. Financial gulf between rich and poor have been reduced by schemes like Ayushman Bharat and Biju Swasthya Kalyan Yojana. This study examines public perceptions of service quality in Odisha's government and private hospitals, using Donabedian’s and Gronroos’s models. Conducted in Bhubaneswar, it sampled 80 respondents each from Capital Hospital and SUM Hospital. Results show private hospitals excel in facilities and attention, while government hospitals offer cost-effective care. Insights are vital for policymakers to improve healthcare delivery in Odisha.